The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0104-14282011005000070
|View full text |Cite
|
Sign up to set email alerts
|

A study of the initiator concentration’s effect on styrene-divinylbenzene polymerization with iron particles

Abstract: This paper describes the preparation of magnetic copolymer obtained from suspension polymerization of styrene (Sty) and divinylbenzene (DVB) in the presence of iron particles treated and not treated with oleic acid. The magnetic copolymers were characterized according to their morphology, particle size distribution and magnetic properties. The results show that incorporation of iron particles significantly changed the particles' morphology. All samples presented higher saturation magnetization than the values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…The similar was observed for crosslinked ionic polymers containing strongly 31 and magnetic copolymer obtained from suspension polymerization of styrene and divinylbenzene. 11 Highly developed internal porous structure is advantageous for the metal ions sorption due to the decrease of the mass transfer resistance, facilitation of the metal ions diffusion which consequently provides high adsorption rate and capacity. 32 The SEM-EDS analysis conrmed the presence of all expected elements (C, O, N and Fe).…”
Section: Characterization Of Mpgme and Mpgme-detamentioning
confidence: 99%
See 1 more Smart Citation
“…The similar was observed for crosslinked ionic polymers containing strongly 31 and magnetic copolymer obtained from suspension polymerization of styrene and divinylbenzene. 11 Highly developed internal porous structure is advantageous for the metal ions sorption due to the decrease of the mass transfer resistance, facilitation of the metal ions diffusion which consequently provides high adsorption rate and capacity. 32 The SEM-EDS analysis conrmed the presence of all expected elements (C, O, N and Fe).…”
Section: Characterization Of Mpgme and Mpgme-detamentioning
confidence: 99%
“…10 The most important parameters for application of magnetic copolymers are the size, size distribution, morphology, hydrophobicity/hydrophilicity, density of reactive surface groups and magnetic properties. 11 Our previous studies have shown that PGME-deta due to the presence of numerous functional groups (-OH and -NH 2 ) can be used for binding of metal oxo-anion species, like Cr and Mo. [12][13][14] The sorption ability of PGME-deta towards pertechnetate anions was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Na etapa onde diferentes tipos de suspensão foram utilizados, foi possível verificar que a utilização da técnica de semissuspensão com balão mostrou-se mais eficiente na manutenção da uniformidade do tamanho das microesferas neste sistema, e que o uso da semissuspensão levou a produção de partículas poliméricas com distribuição de tamanho mais estreita do que uma polimerização em suspensão convencional. Estes resultados estão, também, de acordo com a literatura [4,10] . No estudo onde se utilizou diferentes concentrações de DVB foi verificado que o aumento do teor de DVB (20%) também deslocou de maneira significativa o tamanho de partículas para faixas de tamanho maiores em relação ao polímero com 10% de DVB.…”
Section: Microesferas Magnéticas à Base De Poli(metacrilato De Metilaunclassified
“…Há relatos na literatura de que, assim como o uso da semissuspensão, o uso do iniciador AIBN e do agente estabilizante poli(álcool vinílico)(PVA) colaboram para que o tamanho médio de partículas diminua e a curva de distribuição de tamanho médio de partículas fique mais estreita [4,5,9,10] . Além disso, já é bem conhecido na literatura que microesferas poliméricas magnéticas podem apresentar estado de superparamagnetismo com o uso de maghemita (Fe 2 O 3 ) ou magnetita (Fe 3 O 4 ) [8,11].…”
Section: Introductionunclassified
“…These resins have shown great relevance in the field of research and development due to their wide applicability 2 . These applications include biotechnology, biomedical engineering and medicine, drug segmentation, image enhancement in nuclear magnetic resonance, environmental remediation such as bioremediation of contaminated waters and soils, and in metal separation processes 3–7 …”
Section: Introductionmentioning
confidence: 99%